Experiences of Being a Young Female Sami Reindeer Herder: A Qualitative Study from the Perspective of Mental Health and Intersectionality - Kaiser, Niclas; Näckter, Sofia; Karlsson, Maria; Salander Renberg, Ellinor (Journal of Northern Studies, 2016)
Objectives: To explore experiences of what it means to be a young, female Sami reindeer herder in Sweden, a group occupying a unique position in Swedish Sami life, with special focus on intersectionality and exposure to risk factors regarding mental (ill) health. Methods: A qualitative content analysis of semi-structured interviews with 13 strategically selected female reindeer herders (18–35 years old). Results: The participants described a reindeer-herding lifestyle that they find joyful and vital, but is also conflictual and harsh. Genderspecific issues were raised, for example that they unfortunately and unnecessarily have a place other than the heart of reindeer herding reserved for them. Conclusions: The results of this study suggest that the position of women reindeer herders is paradoxical. This position implies not only a pride in Sami culture but also a risk of developing mental health problems which should be addressed in relation to gender, the reindeer-herding lifestyle and ethnicity.